Inhibin B in stromal-cell ovarian tumors - N. V. Lyubimova; A. M. Beishembaev; Yu. S. Timofeev; N. E. Kushlinskii (Успехи молекулярной онкологии)
Background. Tumors of stroma of the sex cord include a family of tumors that are diverse in structure and biological characteristics, including hormone-active ovarian tumors, such as granulosa cell tumor (GCT) of the ovary and a tumor from Sertoli–Leydig cells. For these types of tumors, of particular importance is the analysis of biochemical markers, among which the most promising is inhibin B.The objective of the study. Comparative analysis of inhibin B levels in the blood serum of patients with stromal cell tumors and other types malignancies.Materials and methods. 64 patients with primary ovarian tumors were examined: 31 – GCT of the ovary, 16 – tumors from Sertoli–Leydig cells, 17 – adenocarcinomas. Comparison group – 20 patients with malignant tumors of other localizations, control – 74 healthy women and 37 patients with benign ovarian tumors. Inhibin B was determined in blood serum using the standardized Inhibin B Gen II ELISA (Beckman Coulter, USA) immunoassay.Results. The analysis of inhibin B levels in last days of the luteal phase, show an increase of marker level in patients with GCT and tumors from Sertoli–Leydig cells, while in ovarian adenocarcinomas and malignant tumors of other locations inhibin B secretion doesn’t differ from the control. The sensitivity of inhibin B in diagnostics of GCT was 93.5 %, in tumor from Sertoli–Leydig cells – 81.3 % with specificity – 100 %.Conclusion. Inhibin B is an effective biomarker of GCT and ovarian tumors from Sertoli–Leydig cells, which results must be interpreted according the functional state of the ovaries.